Genome-Wide Association Study for Disease Traits In Wheat and Its Wild Relatives - Fatima, Fizza (Université d'Ottawa / University of Ottawa, 2020)
Wheat is the most widely grown crop in the world and as such, is an essential source of energy and nutrition. The challenges that breeders presently face is to increase production to feed the rising population of the world, while also accounting for climate change, pollution, water and environmental stresses. As genetic uniformity of modern cultivars has increased vulnerability to pests and diseases, the wild relatives of wheat offer a rich source of genetic diversity and stress tolerance traits, that can be harnessed and transferred in to modern wheat. In this study, we used array-based genotyping to explore genetic diversity in 385 domesticated and non-domesticated lines of wheat and their wild relatives. Genetic characterization using the wheat 90K array, and subsequent filtering and validation mapped 9,570 single nucleotide polymorphic markers onto the wheat reference genome. Phylogenetic analyses illustrated four major clades, clearly separating the wild species from the domesticated, and the ancient Triticum turgidum species from modern T. turgidum cultivars. Using this diverse germplasm, a genome-wide association study (GWAS) was performed for leaf rust, the most widespread rust disease of wheat. Identification of novel sources of resistance is necessary to maintain disease resistance and stay ahead in the plant-pathogen evolutionary arms race. GWAS was conducted using eight statistical models for infection types against six leaf rust isolates and leaf rust severity rated in field trials for 3-4 years at 2-3 locations in Canada. Functional annotation of genes containing significant quantitative trait nucleotides (QTNs) identified 96 disease-related nucleotide associated with leaf rust resistance. A total of 21 QTNs were in haplotype blocks or within flanking markers of at least 16 known leaf rust (Lr) resistance genes. The remaining significant QTNs were considered loci that putatively harbor new Lr resistance genes. Future efforts to validate these loci will help understand their role in disease resistance and promote their utility for marker-assisted selection in pre-breeding.
Keywords: Wheat; Leaf rust; GWAS; Genotyping; Single nucleotide polymorphism; Triticum aestivum